Mental health status of health care professionals working in public and private sectors in Visakhapatnam: A cross-section study - Heena D Tiwari; Apurva K Pandya; Rajkiran Salunkhe; Mathew J Maliyi; Anish Nelson; Praveen K Varma; Rahul V C. Tiwari; Priyanka Parhad (Wolters Kluwer Medknow Publications, 2023)
Introduction: The material that is currently available on the psychological issues that doctors deal with is restricted to a few national surveys and certain particular hospital surveys. The motive of the current study was to define the mental health status of medical as well as surgical professionals working in the public and private sectors of Visakhapatnam, Andhra Pradesh, India. Methodology: A self-reported questionnaire survey was used in an observational cross-sectional study to appraise the mental health state of both private and public medical practitioners. The Kessler Psychological Distress Scale (K10) by William C. Menninger was applied. Results: The majority of study participants experienced psychological anguish, showing a substantial difference in the total level of psychological distress. When the Wellinger's Distress and the Kesslers Distress tools were compared, it was found that there was a substantial difference for all the variables taken into account in the current study, including gender, experience, marital status, children, and occupation, designation, and sector of work. Conclusion: Stress and burnout were more prevalent among medical specialists with lower yearly income, young ages, and fewer years of practice. Clinicians and policymakers must be proactive in creating programes that help healthcare professionals cope with stress and burnout.